A Mesh Adjustment Scheme for Embedded Boundaries (Communications in Computational Physics, 2007)
An adaptive meshing technique and solution method is proposed in whicha two-dimensional body-fitted multi-block mesh is locally adjusted to arbitrarily embedded boundaries that are not necessarily aligned with the mesh. Not only doesthis scheme allow for rapid and robust mesh generation involving complex embedded boundaries, it also enables the solution of unsteady flow problems involving bodies and interfaces moving relative to the flow domain. This scheme has been implemented within a block-based adaptive mesh refinement (AMR) numerical frameworkwhich can ease computational expense while maintaining a detailed representation ofthe embedded boundary and providing an accurate resolution of the spatial characteristics of the fluid flow. Rigid body motion and evolving motion due to physicalprocesses are considered. A block-based AMR level set method is used to deal withevolving embedded boundaries. Numerical results for various test problems are presented to verify the validity of the scheme as well as demonstrate the capabilities of theapproach for predicting complex two-dimensional inviscid and laminar fluid flows.